Research on SDN based network virtualization platform and its isolation - Kai ZHANG; Xiaofeng QIU; Xinning ZHU (Dianxin kexue)
The rapid development of cloud computing has recently prompted extensive application of visualization in enterprise-level environments.In addition to server and storage virtualization,network virtualization attracts more and more attention with the application of SDN and OpenFlow.Therewith,software-defined network platforms designed for network virtualization were presented.Firstly,the objectives of the SDN based network virtualization platform were analyzed.Subsequently,the system architectures and principles of four typical network virtualization platforms based on SDN were compared.At last,the safety and isolation mechanism provided by the network virtualization platforms were investigated.